2020
DOI: 10.1161/circheartfailure.120.006971
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Aortic Balloon Pump Bridging to Heart Transplantation

Abstract: Background: This study evaluates the impact of the 2018 allocation policy change on outcomes of orthotopic heart transplantation (OHT) in patients bridged with intra-aortic balloon pumps (IABPs). Methods: Adult (≥18 years) patients undergoing OHT between 2013 and 2019 who were bridged with an IABP were stratified based on temporal relation to the policy change. Univariate analysis was used to compare baseline characteristics and postoperative outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 22 publications
11
80
1
Order By: Relevance
“…The use of IABP has been reported as an effective bridge to transplant strategy in the new system. 23 Our results suggest that there was a shift in clinical practice, physicians who faced the choice of stabilizing an ACHD patient may have preferred to use an IABP. This would allow for a higher status, with broader organ availability, thus significantly increasing the chances of transplantation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The use of IABP has been reported as an effective bridge to transplant strategy in the new system. 23 Our results suggest that there was a shift in clinical practice, physicians who faced the choice of stabilizing an ACHD patient may have preferred to use an IABP. This would allow for a higher status, with broader organ availability, thus significantly increasing the chances of transplantation.…”
Section: Discussionmentioning
confidence: 79%
“…The choice of IABP to support a patient listed for heart transplantation will not only stabilize the patient but will also immediately increase the priority level in the transplant list (status 2). The use of IABP has been reported as an effective bridge to transplant strategy in the new system 23 . Our results suggest that there was a shift in clinical practice, physicians who faced the choice of stabilizing an ACHD patient may have preferred to use an IABP.…”
Section: Discussionmentioning
confidence: 82%
“…Third, we found that whereas the majority of patients were listed at Status 4, most were Status 2 at time of transplantation via use of intra-aortic balloon pumps (IABP), suggesting that this approach to improve prioritization for listing was being used rather than the standardized exceptions laid out by the OPTN (Organ Procurement and Transplantation Network) Review Board [13]. This indicates that centers might benefit from a greater consideration of the specific criteria for this patient population as a means to list at Status 2 urgency level when the clinical benefit from an IABP might be marginal.…”
Section: Plos Onementioning
confidence: 99%
“…Patients who may be best served with LVAD therapy could be discouraged or prohibited from therapeutic options because of the comparatively lower urgency status it confers, and a disproportionately large number of patients offered higher-urgency temporary therapies such as ECMO. This trend forces patients to compete for organs based on clinical deterioration and creates incentives for physicians to withhold potentially life-saving treatment, a scenario akin to withholding dialysis treatment for a renal transplant candidate in clinical decline to optimize the candidate's likelihood of being matched to a donor [32]. In this scenario, the "life-boat" problem acknowledged with the previous system [33] will continue to burden transplant centers with more high-urgency candidates who are not being optimally managed, worsening patient outcomes and organ survival.…”
Section: Present Challenges and Future Researchmentioning
confidence: 99%